Penguatan Kesadaran Produk Halal Bagi Remaja dan Ibu Rumah Tangga di Desa Kedungrejo - Rokhmawati, Dian; Anugrah, Roy; Hariyanto, Agoes; Limgiani, Limgiani; Rahmawati, Mariana Fitri (JAST : Jurnal Aplikasi Sains dan Teknologi, 2024)
The widespread distribution of cosmetic products that have not been certified halal has raised concerns about the content being dangerous to health and unfit for use because of questionable cleanliness. Likewise, for food and beverage products. On the other hand, the pandemic has significantly impacted people's social behavior, including in the economic sector. Both business actors and consumers tend to carry out their business activities online. As a result, food and beverage products and cosmetics that have not been certified halal can be easily obtained and consumed by the public. The biggest consumers of these two types of products are teenagers and housewives. This service program's role in halal awareness education comes into play. The aim is to build halal awareness in the community, especially teenagers and homemakers in Kedungrejo Village, Pakis District, Malang Regency. The method used is educational activities to increase halal understanding and awareness, as well as creating simple information media to accelerate the dissemination of information about halal products. The output of this service program includes a better level of community empowerment (increased understanding of the counseling participants) as evidenced by the pre-test and post-test given, audio-visual work in the form of videos and a poster, Ayo Aware Halal, which is posted on the information board at the hall office Village. This poster was also handed over to the PKK Cadre community so that it could be copied and reread at home.ABSTRAKBeredar luasnya produk kosmetik yang belum tersertifikasi halal, memunculkan kekhawatiran berupa kandungan yang berbahaya bagi kesehatan, dan tak layak digunakan karena kebersihannya yang diragukan. Demikian juga pada produk makanan dan minuman. Di sisi lain, pandemic memberikan dampak cukup signifikan dalam perilaku sosial masyarakat, termasuk dalam sektor ekonomi. Baik pelaku usaha maupun konsumen cenderung menjalankan aktivitas bisnisnya secara online. Akibatnya, produk makanan dan minuman serta kosmetik yang belum tersertifikasi halal tadi dapat dengan mudah diperoleh dan dikonsumsi oleh masyarakat. Konsumen terbesar kedua jenis produk ini adalah remaja dan ibu rumah tangga. Di sinilah peran program pengabdian berupa penyuluhan kesadaran halal ini. Tujuannya adalah membangun kesadaran halal masyarakat terutama remaja dan ibu rumah tangga di Desa Kedungrejo Kecamatan Pakis Kabupaten Malang. Metode yang digunakan adalah kegiatan edukasi untuk meningkatkan pemahaman dan kesadaran halal serta pembuatan media informasi sederhana untuk mempercepat penyebaran informasi mengenai produk halal. Luaran dari program pengabdian ini diantaranya yaitu tingkat keberdayaan masyarakat yang lebih baik (pemahaman peserta penyuluhan yang meningkat) terbukti dari pre-test dan post-test yang diberikan, karya audio visual berupa video dan sebuah poster Ayo Sadar Halal yang ditempel di papan informasi kantor balai desa. Poster ini juga diserahkan kepada komunitas Kader PKK agar dapat digandakan dan dibaca kembali di rumah.